Cbfβ2 deficiency preserves Langerhans cell precursors by lack of selective TGFβ receptor signaling - Tenno, Mari (J Exp Med, 2017)
The mouse Langerhans cell (LC) network is established through the differentiation of embryonic LC precursors. BMP7 and TGFβ1 initiate cellular signaling that is essential for inducing LC differentiation and preserving LCs in a quiescent state, respectively. Here we show that loss of Cbfβ2, one of two RNA splice variants of the Cbfb gene, results in long-term persistence of embryonic LC precursors after their developmental arrest at the transition into the EpCAM(+) stage. This phenotype is caused by selective loss of BMP7-mediated signaling essential for LC differentiation, whereas TGFβR signaling is intact, maintaining cells in a quiescent state. Transgenic Cbfβ2 expression at the neonatal stage, but not at the adult stage, restored differentiation from Cbfβ2-deficient LC precursors. Loss of developmental potential in skin-residential precursor cells was accompanied by diminished BMP7–BMPR1A signaling. Collectively, our results reveal an essential requirement for the Cbfβ2 variant in LC differentiation and provide novel insight into how the establishment and homeostasis of the LC network is regulated.